The impact of the hormone nandrolone decanoate on several physiological parameters of bodybuilders' kidneys (Journal of Humanities and Social Sciences Research, 2023)
The research issue is that many athletes use Nandrolone Decanoate in an unscientific and deliberate manner. This is seen in their outer features, such as acne on the face and body, high temperatures, hysteria, neurological issues, heart difficulties, and renal problems. As a result, the researcher chose to investigate this instance of bodybuilders by conducting scientific laboratory analyses to document the most serious hormonal issues that these athletes face. To guide them down the right route and provide training that is free of health issues. The study intends to determine the effect of training with the hormone nandrolone decanoate on several physiological parameters of bodybuilders' kidneys. The researcher employed the experimental approach of two groups. A group of 14 bodybuilders who attend to gyms reflect the research sample and society. The sample was split into two experimental groups: one with (7) players who used the hormone and one with (7) players who did not use the hormone. Through their continual follow-up in the hall, secrecy was employed to determine the group that used the hormone, and the second group, which did not use the hormone, was also recognized. Following the use of research processes such as tests and pre-measurements, as well as training, following the dimensional tests and measurements, as well as statistical treatments, a set of essential findings that serve the training and health process for bodybuilders emerged. Including the fact that the group that utilizes the hormone Nandrolone Decanoate has an advantage. The group that utilised the hormone looked to have harmed the kidneys by hypertrophy and the vast amount of pollutants that came through the sweeteners that were created on them. As a result, the researcher advises athletes and coaches to avoid using Nandrolone Decanoate due to its harmful and deadly consequences on physical and psychological health.